Le continuum Gibson : le Cyberespace et les récits du Mervyn Kihn de Gibson - Thomas A. Bredehoft (ReS Futurae)
This article examines William Gibson’s concept of cyberspace, as it is elaborated in his novel Neuromancer, in the context of his Mervyn Kihn stories, "The Gernsback Continuum" and "Hippie Hat Brain Parasite." These stories deal directly with present-day survivals of the nineteen sixties and the nineteen thirties ; Gibson’s use of hallucinatory iconography associated with the sixties and "visionary futurism" associated with the thirties in his visual descriptions of cyberspace hints at the relevance of these stories for interpreting the construct of cyberspace. Ultimately, rather than presenting cyberspace as a liberatory, utopian space, as some postmodern theorists would have it, Gibson’s treatment of hallucinatory and futuristic iconographies suggests that cyberspace functions as the embodiment of past "Dreams" of the future, dreams which, Gibson hints, are at least partially responsible for the "near dystopia" of the present.